2012
DOI: 10.1007/s12013-012-9451-1
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Tissue and Urinary Nicotinamide N-Methyltransferase in Bladder Cancer: Potential for the Development of a Urine-Based Diagnostic Test

Abstract: Carcinoma of the bladder is one of the most common urologic malignancies occurring worldwide. Diagnosis and monitoring of bladder urothelial carcinoma (UC) are based on cystoscopy and urinary cytology. However, these diagnostic methods still have some limitations, mainly related to invasive nature and lack of sensitivity. New reliable and non-invasive biomarkers for bladder cancer detection are therefore required. To explore the involvement of enzymes of drug metabolism in bladder cancer, in the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…An enhanced expression of NNMT has been reported in a number of cancers, such as glioblastoma [47], stomach adenocarcinoma [48,49], papillary thyroid cancers [50,51], renal [52,53], and oral squamous cell carcinomas [54][55][56], colorectal cancer [57], bladder [58], lung and pancreatic cancers [59][60][61]. In our previous works, we explored NNMT expression in renal cell carcinoma (ccRCC) [52], oral squamous cell carcinoma (OSCC) [54][55][56], urothelial carcinoma (UC) of the bladder [58] and non-small cell lung cancer (NSCLC) [60]. Although several cancers have been associated with abnormal NNMT expression, its role in cancer cell metabolism remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…An enhanced expression of NNMT has been reported in a number of cancers, such as glioblastoma [47], stomach adenocarcinoma [48,49], papillary thyroid cancers [50,51], renal [52,53], and oral squamous cell carcinomas [54][55][56], colorectal cancer [57], bladder [58], lung and pancreatic cancers [59][60][61]. In our previous works, we explored NNMT expression in renal cell carcinoma (ccRCC) [52], oral squamous cell carcinoma (OSCC) [54][55][56], urothelial carcinoma (UC) of the bladder [58] and non-small cell lung cancer (NSCLC) [60]. Although several cancers have been associated with abnormal NNMT expression, its role in cancer cell metabolism remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As a phase II metabolizing enzyme, NNMT is involved in the biotransformation of many drugs and xenobiotic compounds [6,7,21]. Abnormal NNMT expression has been reported in many human neoplasms including brain, nasopharynx, oral cavity, thyroid, lung, liver, stomach, kidney, bladder and colon [8,9,10,11,12,13,14,15,16,17,18]. Furthermore, a recent study showed that NNMT overexpression was associated with increased radioresistance via regulating nicotinamide metabolism [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is predominantly expressed in liver and weakly expressed in other tissues like kidney, lung, skeletal muscle, placenta, heart and brain [6]. Abnormal expression of NNMT has been found in numerous cancers, including glioblastoma [8], hepatocellular carcinoma [9], thyroid carcinoma [10], gastric cancer [11], renal cell carcinoma [12], colorectal cancer [13], oral squamous cell carcinoma [14], bladder cancer [15], non-small cell lung cancer [16], and nasopharyngeal carcinoma [17]. These results suggest that NNMT may serve as a potential biomarker for tumor diagnosis and a new therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…NNMT is reported to be overexpressed in many neoplasms. In our previous works, we analysed NNMT expression levels in renal cell carcinoma (RCC) ( Sartini et al, 2006 ), in oral squamous cell carcinoma (OSCC) ( Sartini et al, 2007( Sartini et al, , 2012Emanuelli et al, 2010 ), in bladder urothelial carcinoma (BUC) ( Sartini et al, 2013a ) and in NSCLC ( Sartini et al, 2013b ).…”
Section: Introductionmentioning
confidence: 99%